Zoonoses et santé animale: l’homme et la bête - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2006)
Les maladies animales transmissibles à l'homme brisent des vies et ruinent les populations des pays ACP...